Anticipating the Future in an Uncertain Present: How Individuals Living With Medically Unexplained Cognitive Complaints Value Biomarker‐Based Prognostics - Anne‐Fleur van derMeer; Marjan Knippenberg; Denise Visser; Marianne Boenink (Health Expectations, 2025)
ABSTRACT Introduction In research on Alzheimer's disease (AD) individuals experiencing cognitive problems but not satisfying criteria for mild cognitive impairment (MCI) or AD are referred to as having ‘Subjective Cognitive Decline’ (SCD). A small subset of them will progress to a state justifying an AD diagnosis. AD research trying to identify prognostic biomarkers aims to inform individuals labelled with SCD about the future development of their complaints. This paper explores how persons experiencing these cognitive complaints currently anticipate the future and how they would value emerging biomarker‐based prognostic tests. Methods Semi‐structured interviews with 10 individuals experiencing cognitive complaints, some accompanied by their partners. The interviews were coded using ATLAS.ti 22. The exploratory qualitative analysis was conducted using thematic content analysis (TA). Findings The interviewees experience pervasive uncertainty concerning their persistent but medically unexplained cognitive symptoms. Lacking a diagnosis and a prognosis, they anticipate their future considering various scenarios, while mainly acting upon the scenario of developing further cognitive decline/AD dementia. Interviewees often interpret questions about prognostication as asking about predicting the likelihood of a future diagnosis, clearly valuing the latter. Most interviewees are positive, assuming it would help them and their relatives prepare for the future. They have specific ideas about what type of prognostic information would be helpful, usually focusing on how cognitive decline would impact their lives, for example, what activities they will be able to continue to engage in, when they will no longer recognise loved ones or what character they will have as a patient. Conclusion People experiencing unexplained cognitive complaints experience pervasive uncertainty about their situation and future. They clearly value the idea of a test predicting with high certainty whether they will be diagnosed with AD in the future. Regarding prognostication, most interviewees expect that such tests could help prepare for the future. However, there is a discrepancy between the outcomes usually measured in prognostic research (like the expected speed of decline) and the specific outcomes meaningful to our interviewees. In view of this gap, it is important to reconsider whether and how the development of prognostic biomarker tests for people suffering from unexplained cognitive complaints can be better tailored to the needs of these individuals. Patient or Public Contribution During our interviews, we gathered the perspectives of 10 individuals suffering from medically unexplained cognitive complaints on the value of biomarker‐based prognostics. These interviews were the primary data source. Individuals were also involved in the interpretation of our findings and critical evaluation of our preliminary conclusions.